MNEMOTOPOS OF CHERNIVTSI: VERSION OF MODERN UKRAINIAN LITERATURE - Монолатій, І. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article analyzes the features of the Ukrainian modern literary process, in particular, the actualization of the writing about the city as its (city) memory and post-memory. On a particular literary material, it is shown that memory is a transdisciplinary category, a kind of bridge between literary and historical discourses. The works of contemporary Ukrainian literature testify to the politicization of the literature itself created by the Ukrainian authors and the Ukrainian language, as well as the need to develop the meanings and values that would unite Ukrainians today. It is argued that the memory of Chernivtsi as a distinctive marker of the acquired experience of its surroundings, and therefore the construction of the memory of Chernivtsi and its inhabitants for the purpose of constructing the city identity itself, are the discourses of the modern literary process. The author states that further study of the phenomenon of the city (Chernivtsi) as a place of memory, will construct a modern urban cultural tradition, and thus crystallizes the collective mosaic of heterotopy memory not only to the inhabitants of modern Chernivtsi, but also to the entire Ukraine.